2018
DOI: 10.1515/ats-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring morphological variation in tomato (Solanum lycopersicum): A combined study of disease resistance, genetic divergence and association of characters

Abstract: Genetic variation of quantitative traits is a prevalent characteristic among cultivated tomato varieties. Twenty tomato genotypes comprising indigenous varieties and commercial cultivars, cultured in the Western Region of Cameroon were evaluated using fourteen quantitative traits for disease resistance, phenotypic divergence and heritability estimates. The experiment was carried out using a randomized completed blocks design with three replications. Data collections were disease characteristics, plant developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
5
8
0
Order By: Relevance
“…Most importantly, the analysis of variance of this study revealed significant differences for FYP. A significant difference in FYP in tomato was also reported by other studies [19,39]. In this experiment, the higher FYP was found in the genotype AVTO0314 (1.52 kg) followed by GPB0107 (1.35 kg), GPB0120 (1.31 kg) and AVTO9802 (1.29 kg) (Tab.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Most importantly, the analysis of variance of this study revealed significant differences for FYP. A significant difference in FYP in tomato was also reported by other studies [19,39]. In this experiment, the higher FYP was found in the genotype AVTO0314 (1.52 kg) followed by GPB0107 (1.35 kg), GPB0120 (1.31 kg) and AVTO9802 (1.29 kg) (Tab.…”
Section: Discussionsupporting
confidence: 87%
“…Significant variation in NPB was also reported by Sharma et al [37]. While studying tomato germplasm, Kouam et al [19] also reported that the NPB ranges from 3.10 to 8.97.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations